Electric powertrain : energy systems, power electronics & drives for hybrid, electric & fuel cell vehicles /: energy systems, power electronics & drives for hybrid, electric & fuel cell vehicles. (2017) - Hayes, John G, 1964-; Goodarzi, Gordon A
No abstract available